The normalizations and related dynamic processes for two power indexes. Issue 3 (3rd July 2017) - Liao, Yu-Hsien; Liu, Pang-Tung; Chung, Ling-Yun
Abstract: Here, we introduce the normalisations for the marginal index and the Banzhaf–Owen index, respectively. We show that there exists reduced games that could be adopted to characterise these two normalisations. Further, alternative formulations are also proposed by applying excess functions. Based on reduced games and excess functions, we provide different dynamic processes for these two normalisations.